Substitution method please help :3
![Substitution method please help 3 class=](https://us-static.z-dn.net/files/db2/62ebd274b15672309fed20a4f94d442c.png)
Answer:
3x = 14
Step-by-step explanation:
Add the two equations.
5x + (-2x) = 3x
(-y) + y = 0
6 + 8 = 14
3x = 14.
Step-by-step explanation:
5x - y = 6 and -2x + y = 8
1/ 5x - y = 6
=> y = 5x - 6
2/ -2x + y = 8
Substitute 1/ into 2/ we will have:
-2x + (5x - 6) = 8
=> -2x + 5x - 6 = 8
=> 3x = 14
=> x = [tex]\frac{14}{3}[/tex] <=> y = [tex]\frac{52}{3}[/tex]
- However, the question asked for the final equation when adding 5x - y = 6 and -2x + y = 8 => The correct answer will be: 3x = 14